The Socialization and Assistance in the Creation of Business Identification Numbers for Micro, Small, and Medium Enterprises in the Vocational High School Environment - Amalia, Fisy; Fadli , Ahmad; Ramayanti , Putri Noor; Aisha , Neila; Hidayatullah, Syarif; Tjiwidjaja, Halim; Sukardi, Sukardi; Noor , M. Arief; Saputra, Riyawan; Zulkarnain , Nizar; Khatimah, Husnul (Jurnal Pengabdian Masyarakat dan Penelitian Thawalib, 2025)
Micro, Small, and Medium Enterprises (MSMEs) in Indonesia contribute 60% of regional income and absorb 97% of the workforce, yet many do not have a Business Identification Number (NIB). This activity aims to support government programs by improving capacity, access to capital, and business legality. The community service activity was conducted at the Market Day of SMK Nusantara, Ciputat, using the Participatory Action Research approach, involving 15 lecturers and students from STIE Ganesha. Results showed: 85% of participants were satisfied, but 40% faced difficulties using OSS, and 30% desired additional sessions. Participants' suggestions included follow-up programs, digital training, longer activity duration, and collaboration with financial institutions. Recommended follow-up includes continued assistance, digital literacy training, extended activity duration, and broader collaboration to strengthen the impact of the community service for business actors.